Providing Remedy for Corporate Human Rights Abuses Committed Abroad: The Extraterritorial Dimension of Home States’ Obligation Under ICESCR - Tiruneh, Wubeshet (Utrecht Journal of International and European Law, 2023)
International human rights law, as a system underpinned by the Westphalian paradigm, heavily relies on the role of territorial States in the protection of human rights. However, the territorial model that allocates human rights obligations within and between territorial States suffers serious limitations regarding corporate human rights abuses. Host States, within whose territory corporate human rights abuse occurred, are often unwilling and/or unable to hold TNCs liable and provide remedies for victims. This explains why home States are increasingly urged to remove or reduce various barriers and serve as a potential forum for victims to seek and obtain a remedy for corporate human rights abuses committed abroad. However, whether home States should provide a remedy as a matter of legal obligation under international human rights law or just as a domestic policy consideration remains contentious, particularly under human rights treaties containing jurisdictional clauses.1 Against this, the article seeks to highlight how home States’ obligation to provide remedy for abuses committed abroad by corporations incorporated or domiciled within their respective territories is increasingly recognized within the practice of the Committee on ICESCR.